Gordon Thompson at Bell Northern Research - Podmore, Christopher (Canadian Journal of Communication, 1984)
An introduction to the work of Gordon Thompson and his three criteria for judging new information technologies. A refutation of Goldhaber's criticism. An evaluation of Thompson's work and final comments.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjIyMzAvY2pjLjE5ODR2MTBuNGEzNTY